Transvenous endovascular repair of symptomatic type II endoleak following endovascular repair of a ruptured common iliac aneurysm with arteriovenous fistula - Mak, Gerald (J Vasc Surg Cases Innov Tech, 2020)
Arteriovenous fistula (AVF) is an uncommon presentation of ruptured aortoiliac aneurysm (rAIA). Symptomatic persistence of an AVF fed by a type II endoleak after endovascular aneurysm repair (EVAR) for rAIA is rare, with little in the literature to guide practice. We present a novel transvenous approach to treatment of symptomatic type II endoleak after EVAR for rAIA with AVF. A transvenous approach avoids complex arterial access and the need for stenting in the venous system. This technique should be considered in patients with persistent AVF after EVAR with ongoing symptomatic type II endoleak.